Knowledge on popular beliefs of medical staff of the Servicio Desconcentrado Hospital Universitario Pediátrico Dr. Agustin Zubillaga (Boletin Médico de Postgrado, 2020)
This study was based on a quantitative paradigm oriented under descriptive field research. The purpose of this study was to describe knowledge on popular beliefs of patient’s parents of the medical staff who work in the Servicio de Atención Médica Inmediata of the Servicio Desconcentrado Hospital Universitario Pediátrico Dr. Agustín Zubillaga. The sample consisted of 10 doctors and 8 nurses who were given a Likert-scale questionnaire which was validated by the expert judgment technique. The results demonstrate that respondents show a positive view in regards to the fact that patients mothers with beliefs and customs of their ancestors attend the consult, respecting and recognizing their popular belief system; there is a negative view in the use of popular beliefs in medical practice, combination of popular and scientific knowledge and the possibility of integration of popular beliefs into health education. On the other hand, they express a marked positive view in regards to the use of popular belief based on socioeconomic conditions and that the education or values received by them influence the use of these beliefs; similarly, most respondents express a positive view in relation to beliefs and customs leading to poisoning in patients and a negative view in the possibility that these beliefs cure disease.
Keywords: medicine; traditional; hospital; pediatrics; pediatric nurse practitioners; culture; education